2021
DOI: 10.1210/endocr/bqab175
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Requires Hepatocyte PPARγ Expression to Promote Steatosis in Male Mice With Diet-Induced Obesity

Abstract: Thiazolidinediones (TZD) are peroxisome proliferator-activated receptor γ (PPARγ) agonists that may reduce hepatic steatosis through their effects in adipose tissue and therefore have been assessed as potential therapies to treat nonalcoholic fatty liver disease (NAFLD) in humans. However, some studies suggest that expression and activation of hepatocyte PPARγ promotes steatosis and that would limit the benefits of TZD as a NAFLD therapy. To further explore this possibility, we examined the impact of short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…We have previously assessed the effect of hepatocyte PPARγ in the development of steatosis before and after diet-induced obesity is established [14, 16], and before HFCF-induced NASH [13]. In this study, feeding a HFD (60% Kcal from fat) for 34 weeks did not significantly increase liver weight in male or female mice as compared to their LFD-fed littermates ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…We have previously assessed the effect of hepatocyte PPARγ in the development of steatosis before and after diet-induced obesity is established [14, 16], and before HFCF-induced NASH [13]. In this study, feeding a HFD (60% Kcal from fat) for 34 weeks did not significantly increase liver weight in male or female mice as compared to their LFD-fed littermates ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 70%
“…Similarly, the expression of PPARγ is also increased in the livers of mouse models with NAFLD [1323]. Our group has recently reported that the loss of hepatocyte-specific expression of PPARγ (Pparg ΔHep ), before and after the development of diet-induced obesity in adult male mice, reduced diet-induced liver steatosis [14, 16] . Furthermore, we have shown that Pparg ΔHep reduced the progression of steatohepatitis in mice fed a methionine and choline deficient diet [15], and NASH in mice fed a high fat, fructose and cholesterol (HFCF) diet [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At week 24, thermoneutrality accelerated NASH (NAS score: 6 at 29°C compared with 4 at 22°C, hepatocyte ballooning) and fibrosis development (fibrosis stage: 1C at 29°C compared with 1A at 22°C, increased expression of Col1a1 and Collagen Type IV Alpha 1 Chain); however, housing temperature did not further affect adiposity or parameters of insulin resistance. These robust models have also been shown to be an effective tool for identifying the key cell types that are involved in the pathogenesis of NAFLD ( 37 ), therapeutic targets such as hepatic thyroid hormone receptor β ( 38 ), and characterizing therapies for NAFLD with drugs and compounds such as nitro-oleic acid ( 30 ), rosiglitazone ( 39 ), and incretin ( 40 ) among others.…”
Section: Micementioning
confidence: 99%
“…Rosiglitazone is categorized in a class of drugs known as 'thiazoledinediones' or 'glitazones', which sensitize the cells in the body to the action of insulin 5 . It is a PPAR-γ (peroxisome proliferator-activated receptor-) agonist that has been shown to have anti brotic and anti-in ammatory effects in some renal diseases 6 .…”
Section: Introductionmentioning
confidence: 99%